Distributed Measurement System with GPS Synchronisation and Its Use in Electric Traction - Hrbac, Roman; Kolar, Vaclav; Mlcak, Tomas (Elektronika ir elektrotechnika, 2015)
This paper deals with distributed measurements in power electrical engineering. The word “distributed” means that the measurement is carried out simultaneously in different locations. Distance between these locations can be tens of kilometers or more. For a long time, the authors have been performing electrical measurements in electric traction, especially in electrified railways. Due to the extensiveness of the railway network, it is very important to find the solution of this problem. After a thorough examination of the subject, the authors have developed computer based measuring apparatuses and GPS based synchronizers. This paper describes the creation of the GPS synchronizer as well as a post-processing data synchronization method. The concluding part includes an example of this apparatus being practically used while carrying out measurements in a railway traction transformer substation and on track circuits. Some interesting measurement results, as well as their analysis, are also presented here. DOI: http://dx.doi.org/10.5755/j01.eee.21.6.13750